Historia del Psicoanálisis - Grotjahn, Martin (1968)
Contiene: Vol. 1: Abraham, Frerenczi, Rank, Jung, Adler; Vol. 2: Jones, Federn; Vol. 3: Pfister, Sanchs, Wodf; Vol. 4: Task, Rado, Reik; Vol. 5: Klein, Simmel; Vol. 6: Reich, Fenichel, Horney; Vol. 7: Erickson